2019
DOI: 10.5005/jp-journals-10071-23265
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Burnout among Intensive Care Unit Healthcare Professionals in an Indian Tertiary Care Hospital

Abstract: Intensive care unit (ICU) healthcare professionals work under a stressful environment which can lead to burnout syndrome. We conducted this study to evaluate the prevalence of stress and burnout syndrome among doctors and other healthcare professionals in ICU. We also evaluated the individual contributing factors for stress and burnout syndrome among these ICU healthcare workers. The cross-sectional survey was conducted among the healthcare professionals (doctors, nurses, clinical pharmacists, respiratory ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
(37 reference statements)
1
11
0
1
Order By: Relevance
“…When we considered the cut-off value for HCPs given by Peterson et al [ 12 ], 71.66% of HCPs had high exhaustion and around 80% of HCPs had high disengagement. Similar results were found by Saravanabavan et al [ 13 ], i.e., high level of burnout in around 80% of the HCPs working in the ICUs of a tertiary care hospital. A study done by Guntupalli et al [ 14 ] showed that between 50% and 60% of Indian ICU HCPs show a moderate to a high degree of burnout.…”
Section: Discussionsupporting
confidence: 90%
“…When we considered the cut-off value for HCPs given by Peterson et al [ 12 ], 71.66% of HCPs had high exhaustion and around 80% of HCPs had high disengagement. Similar results were found by Saravanabavan et al [ 13 ], i.e., high level of burnout in around 80% of the HCPs working in the ICUs of a tertiary care hospital. A study done by Guntupalli et al [ 14 ] showed that between 50% and 60% of Indian ICU HCPs show a moderate to a high degree of burnout.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported a prevalence of 23.3% in neonatal intensive care nurses ( n = 30) and 69% ( n = 140) in ICU nurses. [ 11 12 ] A study with a small sample size reported 8% ( n = 2) prevalence in ICU nurses. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…have also reported statistically significant correlation between job satisfaction among Indian critical care nurses and burnout. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When nurses experience emotional burnout, they often avoid stressful situations (Chen et al, 2020). Due to long working hours, frequent night shifts and difficult-to-manage patients, 80% of ICU nurses experience stress and burnout, and 38% of them plan to leave the ICU within the next year (Saravanabavan, Sivakumar, & Hisham, 2019). Tzeng et al (2016) showed that nurses with emergency or intensive care experience performed better in emergencies, indicating that those nurses were more likely to be prepared an epidemic.…”
Section: Surgical Nurses Were More Willing Than Icu Nurses To Partimentioning
confidence: 99%